National Dialogue of Ethiopia: is it on the right track? - Dehinasew Shemelis Andualem (European Scientific Journal, ESJ, 2022)
National dialogues are nationally owned political processes made when there happen profound political crisis that the existing government of a given country cannot solve. Ethiopia too is on the process of conducting national dialogue. This paper analyses the ongoing process of the dialogue against national dialogue principles that the United States Institute of Peace, Berghof Foundation, and others use to predict the success or the failure of a national dialogue. The data were collected from secondary sources such as books, televisions channels, websites, and so on. Then the collected data were qualitatively analyzed to evaluate the process of the dialogue. After analyzing the views of political elites, and other concerned citizens of the country towards the actual process of Ethiopia’s national dialogue in terms of the principles used as yardsticks, the paper concludes that the ongoing process of the planned national dialogue of Ethiopia is not on the right way to achieve the desired goal.